Antioxidant Activity of Bioactive Constituents from Crude Palm Oil and Palm Methyl Ester - Ahmad Gazali Sofwan Sinaga; Donald Siahaan (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2019)
Palm oil has many minor components that can act as natural antioxidant. It contains carotenoid and vitamin E. This research was conducted to determine antioxidant activity of non-polar extract from crude palm oil and fatty acid methyl ester. The oil extract obtained from crude palm oil by solvent extraction with hexane (CPO) and transesterification method followed by solvent extraction with hexane (PME). Carotene content from non-polar extracts were analyzed by using UV-visible spectrophotometer, while carotene composition (?- and ?-carotene) and vitamin E (tocopherol and tocotrienol) compositions were analyzed by using high performance liquid chromatography. Glycerides and esters content was analyzed by gas chromatography. Antioxidant activity of oil extract was determined by using 2,2’-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay method. Result revealed that PME has higher content carotenoid and vitamin E than CPO. As expected, the concentration of carotenoid and vitamin E in PME increased with transesterification process. Results also showed that all of non-polar extracts exhibited antioxidant activity significantly, as proven by inhibitory concentration 50% (IC50) of PME and CPO is 5.9 µg mL-1 and 15.6 µg mL-1. It is suggested that the presence of carotenoid and vitamin E may have a potential effect as natural antioxidant.